Polyarticular hypermobility and its consequences in rowers and swimmers: a preliminary report - Gębska, Magdalena; Weber-Nowakowska, Katarzyna; Oklejak, Michał; Boćkowski, Radosław; Żyżniewski, Jakub; Żyżniewska-Banaszak, Ewelina (Akademia Wychowania Fizycznego w Poznaniu)
Practicing competitive sports by people with joint hypermobility syndrome carries an increased risk of injury. For such athletes it is important to establish a correct diagnosis and modify their training programs in order to minimize the risk of injury during training or competition. The aim of this study was to evaluate the prevalence of polyarticular hypermobility and its consequences in rowers and swimmers. The study sample comprised 15 male rowers 15 male swimmers. A questionnaire survey assessing the knowledge and awareness of hypermobility and its complications was carried out. In order to determine the prevalence of hypermobility in the athletes under study the Beighton and Brighton scores were used. The results of the study suggest that hypermobility in the joints is statistically more prevalent in swimmers than in rowers. Also, the swimmers suffered from injuries and pain within the musculoskeletal system more often than the rowers. Swimmers are more prone to polyarticular hypermobility. It is therefore essential to perform tests to detect joint hypermobility in this group of athletes. It is necessary to develop and introduce special training programs for athletes with elastopathy, which will help to protect their joints against overloads and injuries. When selecting children and young people for various sports, the applied system of medical examinations should include a physiotherapeutic musculoskeletal examination for the presence of polyarticular hypermobility
Keywords: hypermobility; rowers; swimmers; injuries insports; physiotherapy